How renewable energy consumption contribute to environmental quality? The role of education in OECD countries. (20th September 2020) - Zafar, Muhammad Wasif; Shahbaz, Muhammad; Sinha, Avik; Sengupta, Tuhin; Qin, Quande
Abstract: Designing a comprehensive policy framework for ascertaining sustainable development is a problem faced by most of the countries around the globe, and the developed nations are no exception to that. Environmental awareness-oriented policy design for achieving sustainable development goals is a challenge for the developed nations, and there lies the contribution of this study. This study analyzes the impact of renewable energy on carbon emissions, in presence of education, natural resource abundance, foreign direct investment, and economic growth for the Organization for Economic Co-operation and Development countries over the period of 1990–2015. Second generation methodologies are adapted for the empirical estimation. The results show the stimulating role of renewable energy consumption in shaping environmental quality. Education declines carbon emissions. Natural resource abundance and foreign direct investment deteriorate environmental quality. Moreover, the time series individual country analysis also confirms that renewable energy has a positive impact on economic growth. The heterogeneous causality analysis reveals the feedback effect, i.e., bidirectional causal associations among carbon emissions, education, and renewable energy consumption. This empirical evidence suggests that countries should increase investment in education and renewable energy sectors and plan for research and development in renewable energy for ensuring environmental sustainability. Graphical abstract: Image 1 Highlights: This study analyzes the impact of educational attainment on carbon emissions. Study has been done for 27 OECD countries over the period of 1990–2015. Results show stimulating role of educational attainment in shaping environmental quality. Natural resource abundance and FDI deteriorates environmental quality.